The Influence of Different Potato Sowing Schemes of the Variety "Belarusian Early" On the Ecology of Biomass Formation and Yield - Arisovich, Tureev Abat (American Journal of Biology and Natural Sciences, 2025)
In recent years, potato production in the Republic of Uzbekistan has increased 3-4 times, but despite this, the consumption of this product by the population is increasing, which is why prices in the markets are rising to a maximum. To solve the problem, vegetable farms need to direct their efforts to increase the acreage, and by improving the elements of cultivation technology to increase its yield, and the owners of household farms should be interested by the state to attract them to potato cultivation.